Krzysztof Ptak. Oczy i twarze: Kornblumenblau – 300 mil do nieba – Cynga - Taras, Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
In this text, I analyze Krzysztof Ptak’s contribution to such films as Kornblumenblau and Cynga by Leszek Wosiewicz, and 300 miles to heaven by Maciej Dejczera. These films belong to a time that can be characterized as a period of “hot times”, when Krzysztof Ptak was interested in using cinematographic methods to the limits of their possibilities. As far as the history of Polish cinema is concerned, it was then that Polish directors were looking for a new language to talk about the Polish past. Wosiewicz and Dejczer avoided the accusation of “americanization” of Polish cinema, which was charged to Władysław Pasikowski. This may be because Krzysztof Ptak was the cinematographer of their films.